Striving towards Normality in Daily Life: A Qualitative Study of Patients Living with Metastatic Gastrointestinal Stromal Tumour in Long-Term Clinical Remission. (6th October 2020) - Fauske, Lena; Hompland, Ivar; Lorem, Geir; Hall, Kirsten Sundby; Bondevik, Hilde
Abstract : Background . This study explored how patients with metastatic gastrointestinal stromal tumour (GIST) experience the psychosocial challenges associated with their disease and its treatment, as well as how that experience influenced their practical, relational, vocational, and existential life. Methods . This qualitative study has an explorative design and applied a phenomenological and hermeneutical approach. We conducted in-depth, semistructured interviews with 20 patients with metastatic GIST in long-term clinical remission. The gathered data were interpreted using a thematic analysis. Results . Living with metastatic GIST, as well as the side effects of the required medication, led to changes that limited the participants' daily life. They expressed how tiredness, impaired memory, and physical challenges were among the detrimental impacts of the disease on their family life, vocational life, social life, and leisure time. Adjustments were necessary to ensure they had sufficient energy to cope with the practical and relational aspects of everyday life. Feelings of uncertainty stemming from drug resistance, disease progression, and the possibility of early death were also experienced as challenging. Half the participants stated that it was difficult to keep negative mental health issues at bay, and all of them considered the time spent waiting for their scheduled follow-up scan to be burdensome. Conclusions . It is important to focus increased attention on how the daily practical and psychosocial life of patients with chronic cancer, including metastatic GIST, is affected by their disease. Doing so might provide health-care workers with clues regarding how best to guide and support such patients throughout their emotional journey and, therefore, to improve their quality of life. As new medical treatments can also prolong survival and induce long-term clinical remission in relation to several other forms of metastatic cancer, the findings concerning GIST reported in this study might have widespread implications.